Incidence and management of sucking pests on Gerbera under protected cultivation - Paladugu Yasavi (Department of Agricultural entomology, College of Agriculture, 2020)
ABSTRACT A study on “Incidence and management of sucking pests on gerbera under protected cultivation” was undertaken in polyhouses of Thiruvananthapuram, Thrissur and Wayanad districts during June 2019 - February 2020. The objectives were to evaluate the response of different gerbera varieties to sucking pests and to evolve effective method for its management. Documentation of pests infesting gerbera in polyhouses of Thiruvananthapuram, Thrissur and Wayanad districts revealed new record of sucking pests viz., aphid, Macrosiphum euphorbia (Thomas), scales, Icerya sp., mealybugs, Planococcus citri (Risso) and thrips, (Scirtothrips dorsalis and Haplothrips sp.). Natural enemies viz., spiders recorded and identified were Plexippus paykulli (Audouin), Theridion sp., Oxyopes birmanicus (Thorell) and Ptocassius sp. Other sucking pest documented was mites, Tetranychus sp. Experimenttwasycarried outein CRD to evaluate varieties for field tolerance to sucking pests. Among the five varieties of gerbera, Beaudine (26.85) and Esmara (30.79) harbour less number of thrips compared to other varieties, while Cappablanca (58.52) variety was more susceptible to thrips compared to Sona (50.62) variety. In case of mealybugs, the lower population of mealybugs was recorded in Beaudine (31.25) followed by Cappablanca (41.62), Esmara (42.62) and Aquamelone (48.50) and they were significantly on par. Sona recorded higher population of mealybugs (97.81) which was significantly different from others and hence Sona has selected for further study. Experimentywasycarried outuin CRD to evaluate the efficacy of five treatments viz., spiromesifen 22.9%SC @ 1 mL L-1, L. lecanii@ 20g L-1, fish jaggery 0.5% @ 5 mL L-1, fipronil 40%+ imidacloprid 40%WG @ 175+175g a.i ha -1 and thiamethoxam 25%WG @ 50g a.i ha-1 against sucking pests infesting gerbera. The results revealed that spiromesifen 22.9%SC @ 96g a.i ha-1 was the best treatment in reducing the population (99.61 %) and leaf infestation (12.77%) of mites in gerbera after 15 days of treatment. 97 The lowesteincidence of thrips was recorded in fipronil 40% + imidacloprid 40% WG @ 175+175g a.i ha -1 treated plants (100%) at 7DAT and reduced 20.71per cent reduction in leaf infestation at 15DAT. The next best treatment was spiromesifen 22.9%SC @ 96g a.i ha-1 and thiamethoxam 25%WG @ 50g a.i ha-1 which recorded 98.83 per cent and 95.04 per cent reduction of thrips population at 7DAT. The study could concluded that the Beaudine variety of gerbera harbour less number of thrips and mealy bugs, while Cappablanca variety found susceptible to thrips and Sona variety was susceptible to thrips and mealy bugs. The studies on management of pests of gerbera revealed that the application of spiromesifen 22.9%SC @ 96g a.i ha-1 could effectively manage mite, Tetranychus sp. and thrips, S.dorsalis in gerbera.